(untitled) (Indian Journal of Chemistry (IJC), 2025)
Supramolecular superstructures controlled by pH dependent self-assembly of octaphosphonatetetraphenyl-porphyrin-1 (OPP-1) in aqueous solution. UV-vis absorption spectroscopy shows decreasing in the intensity of OPP-1 in the pH range 3.0 to 6.0, which is correlated to H-type aggregates. However, absorption shifted to bathochromic (red-shift) under the influence of pH 8.0-11.0 range, which is typical for a J-type aggregates in absorbance spectrum as a result of supramolecular self-organisation constructed as compared to free OPP-1 (molecules transitioned to a monomeric positions), in which OPP-1 aggregated outside the surface pH 8.0-11.0 range similar to growth of worm-like micelles. However, at pH range 3.0-6.0, OPP-1 aggregated inside the surface. Self-assembled OPP-1 were visualised on silicon wafer by Scanning Electron Microscopy (SEM), it clearly shows that petite rod-like aggregates at pH = 5.0 and 6.0. Interestingly, OPP-1 assembled into directional growth produces worm-like micelles aggregates at pH = 8.0 and 9.0, respectively. The main driving force of assembled supramolecules are basically based on H-bonding, p-p stacking between central core of porphyrin. Finally, Dynamic light Scattering (DLS) study supports mode of aggregation of short rods and growth of worm-like micelles in basic pH and X-ray diffraction (XRD) study clearly demonstrations self-assembled structures are crystalline in nature. This interesting pH-dependent self-assembly phenomenon is based on OPP-1 (synthetic analogue to natural occurring porphyrins) and could provide basis for development of novel conducting materials as well as biomaterials in future.